Cutting the fuse the explosion of global suicide terrorism and how to stop it - Pape, Robert Anthony 1960-; Feldman, James K. (James Kendrick) (2010)
Almost every, week, suicide bombers attack. We know the danger - suicide attacks kill more people than all other forms of terrorism - and in response we have sacrificed the lives of soldiers and civilians, trillions of dollars, and America's reputation abroad in a futile quest for absolute security. But do we really understand what drives people to deliberately kill themselves on a mission to harm the innocent? "Cutting the Fuse" offers a wealth of new knowledge about the origins of suicide terrorism and strategies to stop it. Robert A. Pape, James K. Feldman, and the Chicago Project on Security and Terrorism have examined every suicide terrorist attack worldwide from 1980 to 2009. Their work fundamentally changes how we understand the root causes of the most important terrorist campaigns today and reveals why the War on Terror has been ultimately counterproductive. Since 2004, the number of suicide attacks - whether within a country or transnational - has grown with shocking speed.